2010
DOI: 10.1177/1359786810385491
|View full text |Cite
|
Sign up to set email alerts
|

Review: A systematic review of hypothalamic-pituitary-adrenal axis function in schizophrenia: implications for mortality

Abstract: There is convincing evidence that environmental stress plays a significant role in modifying both mental and physical health. The biological mechanisms linking stress to ill health are not fully understood, but significant evidence points to a central role of the stress axes; the hypothalamic–pituitary–adrenal (HPA) axis and the sympathetic nervous system. Together these two systems link the brain and the body and are crucial in maintaining homeostasis as well as improving an organism’s survival chances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(166 citation statements)
references
References 226 publications
3
161
2
Order By: Relevance
“…Previous studies have found correlations between PANSS subscales and blood cortisol even in the absence of differences between the cortisol levels of patients and controls. 28,31 Taken together, these data suggest that the dynamics of cortisol concentration over time might be more important than the concentrations per se in predicting psychopathology.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have found correlations between PANSS subscales and blood cortisol even in the absence of differences between the cortisol levels of patients and controls. 28,31 Taken together, these data suggest that the dynamics of cortisol concentration over time might be more important than the concentrations per se in predicting psychopathology.…”
Section: Discussionmentioning
confidence: 86%
“…A longitudinal study conducted in FEP patients showed that those who did not respond to 12-week antipsychotic treatment already had at illness onset a significant lower CAR (measured in the saliva) compared with patients who responded [72]. It was observed that at psychosis onset CAR predicts subsequent treatment response, as blunted CAR shown a tendency to remain unchanged with antipsychotic treatment [75]. On the whole, it is possible that more blunted CAR can possibly be a trait marker, reflecting a more severe illness not modifiable by treatment [33,72,75].…”
Section: Hormones Possible Biological Markers?mentioning
confidence: 99%
“…66 The stress response system plays an important role in brain energy metabolism by increasing the availability of Patients with schizophrenia present long periods of increased cortisol secretion, especially those experiencing their first episode and not previously treated. 67 They also show low reactivity to stress, with a blunted cortisol response to psychosocial stress. 67 In BD, studies have shown altered corticotropin-releasing hormone (CRH) secretion previous to symptom onset, 68 cortisol hypersecretion in euthymia, depression and mania, 69 and a non-normalization of the HPA axis after symptom remission.…”
Section: Metabolic Systems Involved In the Pathophysiology Of Psychiamentioning
confidence: 99%
“…67 They also show low reactivity to stress, with a blunted cortisol response to psychosocial stress. 67 In BD, studies have shown altered corticotropin-releasing hormone (CRH) secretion previous to symptom onset, 68 cortisol hypersecretion in euthymia, depression and mania, 69 and a non-normalization of the HPA axis after symptom remission. 70 Overall, evidence points to disturbances of the stress response system as a trait of both illnesses.…”
Section: Metabolic Systems Involved In the Pathophysiology Of Psychiamentioning
confidence: 99%